The structure design of mobile charging piles - Wu Zhongming; Wang Lanxin; Lu Junfeng; Sun Li (Open Physics, 2022)
The simple instalment of mobile charging piles benefits for its convenient layout, while dynamic arrangements of those charging piles through mobile mode make up for the insufficient number of fixed charging piles, which meets the growing charging demand under the increasing popularity of electric vehicles. According to the application requirements of mobile charging piles, CATIA software was used to model the structure, of which strength and reliability were analysed under four load conditions. Our results have demonstrated that the maximum deformation value of the structure is 3.07 mm, and the maximum stress is 134.41 MPa, which is within the safety range of the selected materials. In addition, the gravity centre of the charging pile is located at the bottom of the structure, and thus the stability meets the requirements. Taken together, our research provided a beneficial reference for future engineering practice.